Meta-Analisis Pengaruh Penggunaan Media Roda Putar Terhadap Hasil Belajar Matematika di Sekolah Dasar - Solichah, Mar'atus; Akhwani, Akhwani; Hartatik, Sri; Ghufron, Syamsul (Universitas Negeri Malang, 2020)
This study aims to analyze the effect of the use of the wheel media on student mathematics learning outcomes in elementary schools. This research uses meta-analysis method. Research data on the use of the wheel media is analyzed deeply to find the effect of the wheel media on the results of learning mathematics. This research begins by formulating research topics, exploring relevant research results for analysis. Data were analyzed using quantitative descriptive analysis. The results showed the use of the wheel media in learning mathematics in elementary schools could improve mathematics learning outcomes of elementary school students. Based on the results of the analysis of the use of the wheel media in mathematics learning in elementary schools can improve mathematics learning outcomes of elementary school students starting from the lowest 5.57% to the highest 545.67% with an average of 121.83%.Â Penelitian ini bertujuan untuk menganalisis pengaruh penggunaan media roda putar terhadap hasil belajar matematika siswa di Sekolah Dasar. Penelitian ini menggunakan metode meta analisis. Data-data hasil penelitian penggunaan media roda putar dianalisis secara mendalam untuk menemukan pengaruh media roda putar terhadap hasil belajar matematika. Penelitian ini diawali dengan merumuskan topik penelitian, menelusuri hasil penelitian yang relevan untuk dianalisis. Data dianalisis dengan menggunakan analisis deskriptif kuantitatif. Hasil penelitian menunjukan penggunaan media roda putar pada pembelajaran matematika di Sekolah Dasar mampu meningkatkan hasil belajar matematika siswa Sekolah Dasar. Berdasarkan hasil analisis penggunaan media roda putar pada pembelajaran matematika di Sekolah Dasar mampu meningkatkan hasil belajar matematika siswa Sekolah Dasar mulai dari yang terendah 5,57% sampai yang tertinggi 545,67% dengan rata-rata 121,83%.